Optical bistability in ferroelectrics via two wave mixing / Muhammad Asif Ahmad Khushaini - Ahmad Khushaini, Muhammad Asif (2017)
Optical bistability (OB) is the phenomenon resulted from the interaction of the light source with the third order nonlinear material. OB is believed to have promising applications as basic elements for future optical computers and optical switches. In the recent years, obtaining the OB via wave mixing process attracted significant interest due to the influences of wave interaction that occurring inside the material may enhance the OB characteristic. This study investigates the OB resulting from a degenerate two-wave mixing (TWM) process in a single layer of Kerr nonlinear ferroelectric material. The nonlinear process is mathematically described by a nonlinear coupled-wave (CW) equations propagating across the ferroelectric. In the first part, we investigate the influence of the Slowly Varying Envelope Approximation (SVEA) on the evolution of the system. The results obtained in this section are compared with the standard available experimental data. Our results from this part clearly demonstrate that the full mathematical model without SVEA is essential to produce a theoretical result that is matched the experimental data as a evident in this thesis. In the second part of this work, we have examined the effect of Self Action nonlinearity on resulting OB. Self Action nonlinearity usually ignored in studying the OB via TWM. Our results show that the Self Action nonlinearity is important to detect the nonlinear response of the OB for several combinations of input parameters.